2021
DOI: 10.1186/s12885-021-08111-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel 10 glycolysis-related genes signature could predict overall survival for clear cell renal cell carcinoma

Abstract: Background The role of glycolysis in tumorigenesis has received increasing attention and multiple glycolysis-related genes (GRGs) have been proven to be associated with tumor metastasis. Hence, we aimed to construct a prognostic signature based on GRGs for clear cell renal cell carcinoma (ccRCC) and to explore its relationships with immune infiltration. Methods Clinical information and RNA-sequencing data of ccRCC were obtained from The Cancer Geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…In line with our findings, overexpression of HS6ST2 has been found to be a poor prognostic factor in several malignant tumors [ 20 , 24 , 30 , 31 , 32 , 33 ]. Interestingly, HS6ST2 has been recently described as part of a novel 10 glycolysis-related gene signature to predict overall survival in ccRCC [ 34 ]. Liep et al [ 35 ] found that overexpression of miR-145-5p and miR-141-3p could inhibit the migration and invasion of RCC cells by decreasing HS6ST2 expression in cellular transfection experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, overexpression of HS6ST2 has been found to be a poor prognostic factor in several malignant tumors [ 20 , 24 , 30 , 31 , 32 , 33 ]. Interestingly, HS6ST2 has been recently described as part of a novel 10 glycolysis-related gene signature to predict overall survival in ccRCC [ 34 ]. Liep et al [ 35 ] found that overexpression of miR-145-5p and miR-141-3p could inhibit the migration and invasion of RCC cells by decreasing HS6ST2 expression in cellular transfection experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the individual heterogeneity of the TME, it is urgent to quantify the scoring pattern of individual tumours and establish an effective treatment and prognosis evaluation model for patients with ccRCC. Although previous studies have explored the value of different signatures in the prognostic evaluation of ccRCC, their validity remains limited ( 31 , 32 ). Meanwhile, the analysis of cell-cell communication reveals that the expression of ligands and receptors and the type of interaction vary in different tumour types.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Wu et al reported that redox-related genes were associated with immune infiltration and could accurately predict ccRCC prognosis (39). Xing et al identified 10 glycolysisrelated genes that predicted OS for ccRCC patients (40).…”
Section: Discussionmentioning
confidence: 99%